Mediterranean Diet Improves Plasma Biomarkers Related to Oxidative Stress and Inflammatory Process in Patients with Non-Alcoholic Fatty Liver Disease - Maria Magdalena Quetglas-Llabrés; Margalida Monserrat-Mesquida; Cristina Bouzas; Isabel Llompart; David Mateos; Miguel Casares; Lucía Ugarriza; J. Alfredo Martínez; Josep A. Tur; Antoni Sureda (Antioxidants, 2023)
Non-alcoholic fatty liver disease (NAFLD) shows liver fat depots without alcohol consumption. NAFLD does not have specific drug therapies, with a healthy lifestyle and weight loss being the main approaches to prevent and treat NAFLD. The aim was to assess the antioxidant and pro-inflammatory state in patients with NAFLD after 12-month-lifestyle intervention depending on the change in adherence to a Mediterranean diet (AMD). Antioxidant and inflammatory biomarkers were measured in 67 adults (aged 40–60 years old) diagnosed with NAFLD. Anthropometric parameters and dietary intake were measured by a validated semi-quantitative 143-item food frequency questionnaire. The nutritional intervention improved anthropometric and biochemical parameters after a 12-month follow-up. However, decreases in alanine aminotransferase (ALT) and C reactive protein (CRP) were higher in participants with high AMD, which also showed higher improvement in physical fitness (Chester step test) and intrahepatic fat contents. The intervention reduced plasma levels of malondialdehyde, myeloperoxidase, zonulin, and omentin, and increased resolvin D1 (RvD1), whereas the decrease in leptin, ectodysplasin-A (EDA), cytokeratin-18 (CK-18), interleukin-1ra (IL-1ra) and endotoxin was only significant in participants with higher AMD. The current study showed that a one-year nutritional intervention improved main NAFLD features such as body mass index, IFC, liver enzymes, and prooxidant and proinflammatory status. There was also a decrease in the concentration of plasmatic endotoxin, suggesting an improvement in intestinal permeability. These health benefits were more evident in participants that improved AMD to a greater extent. The trial was registered at ClinicalTrials.gov with registry number NCT04442620.